37,000 smallholders implementing low emissions agriculture resulting in 1 Mt CO2e verified mitigation in East Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
In Kenya and Uganda, 37,000 thousand smallholders implemented low-emission agriculture as a result of CCAFS participatory action research on institutional self-sufficiency in carbon projects. In 2014, Vi-Agroforestry, ECOTRUST, and EcoAgriculture Partners developed guidance for projects to design, implement and monitor agriculture carbon projects. Vi Agroforestry and ECOTRUST have used the guidance with their projects throughout the region. To date, 14 agroforestry practices have been implemented on 28,000 ha, resulting in 1 Mt CO2e 3rd-party verified mitigation, with ~70% women participants.